Planning in brazilian public schools in the perspective of interdependent school management - Piacentini, Alexandre Leonardo Simões; Winck, Cesar Augustus; Piacentini, Marcos Tadeu Simões; do Vale, Carlaile Largura (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2017)
This work proposes an analysis of the organizational planning adopted by brazilian public schools, in the face of an interdependent school management construct based on the Contingency Theory's assumptions, intending to offer subsidies to managers and researchers in the area of Administration and School Management. For this purpose, the Direct Money in School Program (PDDE Interativo), a planning tool developed and made available by the Brazilian government in support of management in the public education network, is used as reference. It is considered that the adoption of Interactive PDDE has not provided school management efficiency gains in relation to long-term organizational goals. The guiding question for the study was: How is the methodology of the Interactive PDDE characterized by a school management perspective based on the Contingency Theory? A Case Study Method was used to qualitatively address the object of study. As results, it was identified that (1) the administrative methodologies can be taken as technological variables that influence the organizational structure and, therefore, as contingent factors of the school organization; (2) that the critical points lie in the axis of the organizational environment analysis; (3) and that the drivers for the adjustment of the Interactive PDDE will involve the articulation of the diagnostic dimensions, establishment of objectives and evaluation procedures.